A COMPREHENSIVE REVIEW OF THE PREVALENCE, DETERMINANTS, AND CHALLENGES OF SMALL-CELL LUNG CANCER IN NEVER SMOKERS (The Research of Medical Science Review, 2025)
Small-cell lung cancer is an aggressive neuroendocrine malignancy strongly linked to smoking; however it’s occurrence in never smokers could indicate the influence of some environmental, occupational, genetic/molecular factors which aren’t often considered. This review aims to not only gain a broader picture on small-cell lung cancer but also investigate possible risk factors as well as relevant diagnostic and public health strategies. A comprehensive literature search was conducted using Web of Science, EMBASE and Google Scholar. Primary articles of focus included studies on lung cancer in never-smokers, small-cell lung cancer, risk factors associated with lung cancer in never smokers. Relevant studies were overviewed to identify important information. Study findings indicate several possible risk factors among never-smokers such as occupational exposures (e.g. asbestos, polycyclic aromatic hydrocarbons, wood dust etc.), air pollution, second hand smoke as well as genetic and molecular influences. Findings also suggest possible predilection for older age and female demographic, patients with history of autoimmune diseases and regional variations. According to the findings it is also suggested that the prevalence of never-smoking small-cell lung cancer cases has been on the rise over the past few decades. Understanding the risk factors for small-cell lung cancer among the never-smoking population is critical for refining lung-cancer preventive strategies, diagnostic tools and public health measures.